2011
DOI: 10.1111/j.1556-4029.2011.01821.x
|View full text |Cite
|
Sign up to set email alerts
|

Complex Suicide: An Unusual Case with Six Methods Applied

Abstract: Complex suicides (CSs) are committed by using more than one method. They account for 1.5-5% of all suicides. We present a case of CSs of a 44-year-old man, found dead in the vicinity of his car, in a deserted frozen field. Police investigation excluded homicide, and no medical data confirmed mental illnesses. Autopsy revealed wrist cuts, neck cuts, acid burns in the GI tract, multiple stab wounds to the head by a screwdriver, and several uncertain signs of hypothermia. Toxicology analysis (gas chromatography-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 15 publications
(15 reference statements)
0
16
0
Order By: Relevance
“…The data collected from reviewing the literature concerning suicidal and homicidal injuries are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data collected from reviewing the literature concerning suicidal and homicidal injuries are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…In suicides, the injury is usually single with several hesitation marks near the fatal wound . At the same time, unusual cases are available in the literature, including four suicides in which number of injuries was between 11 and 15 , and five cases with more than 25 wounds, with a maximum of 92 injuries .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, based on the shape of the contusion mark and the finding of two used blank cartridges at the scene of death, the weapon was placed to the skin and fired twice. The heart is often targeted since severe injury to the heart ought to result in a successful suicide attempt . However, in our case, the unusual mechanism of injury by “gas missile” indicated that the pericardium remained undamaged, thus allowing the victim to fire another gunshot.…”
Section: Discussionmentioning
confidence: 80%
“…In unplanned complex suicides selfinflicted injuries by a sharp instrument, especially cuts of the wrists, are often found as the primary act of suicide. 2 Petkovic´et al 3 and Nikolic´et al 4 reported combination of non-fatal wrist cuts with other suicide methods. Serafettin et al, 5 in their series of complex suicides, mentioned combinations of wrist cutting along with medicine overdose or gunshot wounds to other parts of the body.…”
Section: Discussionmentioning
confidence: 97%